PERSPEKTIF SAAT TEDUH DAN AMANAT AGUNG DALAM MATIUS 28:19-20 DENGAN KOMSEL - Jonathan Jono; Rikardo P. Sianipar (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2023)
This research aims to determine the relationship between the shady times of the congregation and of the great commission according to Matthew 28:19-20 with the cell community at Abbalove Ministries Greenville Maizonette Jakarta. Shady times are an important part of the spiritual of the congregation. For through a quiet time the congregation will experience personal communion with God. But in the practice of pluralizing, it is found that some congregations do not really give time to shady times. Similarly, the commission that aims to evangelize and make disciples is the command of the Lord Jesus but not all believers do the commission. This research uses quantitative methods with correlational techniques. Researchers distributed questionnaires to 102 respondents on a likert scale. Then the received data is processed and analyzed using SPSS Version 21. The results of this study show that there is a significant and strong relationship between the shady time of the congregation and the cell community at Abbalove Ministries Greenville Maizonette Jakarta. There is a significant and strong connection between the understanding of commission according to Matthew 28:19-20 and the cell community at Abbalove Ministries Greenville Maizonete Jakarta. So it can be concluded, that we long for all congregations to be involved in the cell community, to be diligent in personal meditation and to understand the great commission according to Matthew 28:19-20.